PEMBERDAYAAN KELUARGA DENGAN TINGKAT KECEMASAN PASIEN RAWAT INAP DI RSUD DR MOEWARDI - Nuriyah Yuliana; Triana Mirasari (Jurnal Infokes, 2020)
Background: Family support, both directly and indirectly can reduce anxiety in someone who is treated in hospital. Emotional family support feels comfortable because they are cared for, loved, valued, become confident, and are able to see and grow hopes for the future so they are able to ward off and reduce anxiety. Objective: To find out the empowerment of families with the anxiety level of inpatients at RSUD Dr. Moewardi. Method: This study uses analytical research methods with cross sectional approach. Sampling using a purposive sampling technique, with a number of research samples of 57 respondents who met the criteria for population in this study, while the research instrument used a questionnaire. Bivariate analysis uses Kendall's Tau correlation analysis. Results: Bivariate test results with Kendall's Tau obtained z_count value of 3.83 with a significance number ρ_value = 0,000, from the results known z_count (3.83)> Z_table (1.96) and significance value α <005 so that Ho was rejected and Ha accepted, then there is a significant relationship between family empowerment with anxiety levels in hospitalized patients at RSUD Dr. Moewardi. Conclusion: There is a relationship between family empowerment and the level of anxiety in hospitalized patients at RSUD Dr. Moewardi.